Prospective study on loss of signal on the first side during neuromonitoring of the recurrent laryngeal nerve in total thyroidectomy. Issue 5 (23rd January 2013) - Sitges‐Serra, A.; Fontané, J.; Dueñas, J. P.; Duque, C. S.; Lorente, L.; Trillo, L.; Sancho, J. J.
Abstract Background Staged thyroidectomy has been recommended when loss of the signal from intraoperative nerve monitoring is observed after first‐side dissection of the recurrent laryngeal nerve. There is no high‐quality evidence supporting this recommendation. In addition, it is not clear whether signal loss predicts postoperative vocal cord paralysis. Methods This was a prospective observational study of consecutive adult patients undergoing neuromonitored total thyroidectomy for either malignancy or multinodular goitre. The prevalence of first‐side loss of signal was recorded. Surgery was completed, and vagus and laryngeal nerves on the first side were rechecked at the end of the procedure. Results Two‐hundred and ninety patients were included. Loss of signal on the first side was noted in 16 procedures (5·5 per cent). Thyroidectomy was completed and, at retesting, 15 of 16 initially silent nerves recovered an electromyographic signal with a mean(s.d.) amplitude of 132(26) mcV. Mean time to recovery was 20·2 (range 10–35) min. In no patient was the signal lost on the opposite side. Only three of 15 nerves with a recovered signal were associated with transient vocal cord dysfunction. Conclusion After loss of signal of the recurrent laryngeal nerve dissected initially, there was a 90 per cent chance of intraoperative signal recovery. In this setting, judicious bilateral thyroidectomy can be performed without risk of bilateral recurrent nerve paresis.